2007
DOI: 10.1074/jbc.m607008200
|View full text |Cite
|
Sign up to set email alerts
|

αVβ6 Is a Novel Receptor for Human Fibrillin-1

Abstract: Human fibrillin-1, the major structural protein of connective tissue 10 -12 nm microfibrils, contains multiple calcium binding epidermal growth factor-like domains interspersed with transforming growth factor ␤-binding protein-like (TB) domains. TB4 contains a flexible RGD loop that mediates cell adhesion via ␣V␤3 and ␣5␤1 integrins. This study identifies integrin ␣V␤6 as a novel cellular receptor for fibrillin-1 with a K d of ϳ0.45 M. Analyses of this interaction by surface plasmon resonance and immunocytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…1B) (27). Identical results were obtained using the TGF-␤-responsive plasmid (CAGA) 12 MLP-Luc, (data not shown). Quantitative differences in Smad2/3 signaling between VSMC of different mutant genotypes and between individual cell strains of the same mutant genotype are likely to reflect variances in disease progression and penetrance (Fig.…”
Section: Smad2/3 Signaling Is Constitutively Active In Fbn1 Mutant Vsmcsupporting
confidence: 69%
See 2 more Smart Citations
“…1B) (27). Identical results were obtained using the TGF-␤-responsive plasmid (CAGA) 12 MLP-Luc, (data not shown). Quantitative differences in Smad2/3 signaling between VSMC of different mutant genotypes and between individual cell strains of the same mutant genotype are likely to reflect variances in disease progression and penetrance (Fig.…”
Section: Smad2/3 Signaling Is Constitutively Active In Fbn1 Mutant Vsmcsupporting
confidence: 69%
“…The choice of Fbn1-null cells was based on the assumption that the extremely rapid physical collapse of the aortic wall in mgN/mgN mice might eliminate the confounding effects of secondary cellular events that characterize late onset vascular disease in the other two mouse models of MFS (5-7). The results revealed that inhibition of either p38 MAPK or JNK activity negatively affects the expression of the p3TP-Lux and (CAGA) 12 MLP-Luc reporter plasmids ( Fig. 2A) (data not shown).…”
Section: Smad2/3 Signaling Is Constitutively Active In Fbn1 Mutant Vsmcmentioning
confidence: 93%
See 1 more Smart Citation
“…5 Attachment of cells to fibrillin-1 is mediated via the integrin receptors avb3, a5b1, and avb6. [6][7][8] Recently, a8b1 integrin was also described to interact with fibrillin-1. 9 In the kidney, the a8 integrin chain is expressed on vascular smooth muscle cells and mesangial cells.…”
mentioning
confidence: 99%
“…These mutations are located in TB4 relatively close to the sole integrin-interacting RGD sequence in fibrillin-1 [87][88][89]. A significant loss of attachment and spreading of human foreskin dermal fibroblasts to mutated fibrillin-1 fragments, was observed for these mutations suggesting that the fibrillin-1 interaction with integrins avb3 and/or a5b1 was affected [42].…”
Section: Mutations That Do Not Lead To Marfan Syndromementioning
confidence: 98%